Renstra Bisnis Spare Parts Otomotif Berbahan Karet di CV Regina Eka Pratiwi - Innas Rovino Katuruni; Arief Daryanto; Agus Maulana (MANAJEMEN IKM: Jurnal Manajemen Pengembangan Industri Kecil Menengah, 2015)
Automotive industry is one of the rapidly-growing industry in Indonesia. According to statistical data, sold vehicles per annum are growing more. The increasing demand of vehicles can be able to influence the demand of spare parts. One of the operating company that produces made of rubber-spare parts is CV Regina Eka Pratiwi. The growth of automotive environment in Indonesia doesn’t support the growth of company organization of CV Regina. It is shown by the company performance that can be said as unsatisfactory. This research aimed at analyzing the business condition of CV Regina Eka Pratiwi, formulating the business strategic of CV Regina Eka Pratiwi, recommending the strategic policy and action plan on the strategic business of CV Regina Eka Pratiwi. This research was conducted at CV Regina Eka Pratiwi on April and May 2015. The sample on this research used purposive sampling on the managerial board that is supposed to understand the company condition using support of questionnaire and descriptive-qualitative approach. The step and method used namely to analyze the main cause of company problem, to do Internal Factor evaluation (IFE) and External Factor Evaluation (EFE) analysis, Internal External (IE) matrix and Strengths, Weakneses, opportunities, dan Threats (SWOT) analysis, to formulate priority strategy of the company through Quantitative Strategic Planning Matrix (QSPM) method, and to evaluate the company strategies. By the analysis output, it is obtained that the company still has many weaknesses. The high opportunity causes the company still able to operate with the existing power. The obtained score in IFE is greater than the strength, the opportunity score in EFE is greater than the threat. Obtained strategy is defense and attack characteristic and the strategy on IE matrix that is harvest and divest strategy. QSPM is used to gain priority strategy that will firstly appplied bu CV Regina